2019
DOI: 10.1038/s41467-019-09261-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth strategy of microbes on mixed carbon sources

Abstract: A classic problem in microbiology is that bacteria display two types of growth behavior when cultured on a mixture of two carbon sources: the two sources are sequentially consumed one after another (diauxie) or they are simultaneously consumed (co-utilization). The search for the molecular mechanism of diauxie led to the discovery of the lac operon. However, questions remain as why microbes would bother to have different strategies of taking up nutrients. Here we show that diauxie versus co-utilization can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 70 publications
10
136
0
2
Order By: Relevance
“…We found that all four of our organisms experienced cases of higher than expected yields on double vs. single nutrients (Supplementary Figure 13), which may reflect capabilities of the organisms to more efficiently fulfill metabolic requirements using multiple nutrients. Our observation parallels previous instances of this effect in microbial growth rates 33,39,40 , which we also corroborated using a timecourse experiment (Supplementary Figure 14). Thus, it seems plausible that the increases in ( we observed with increasing environmental complexity are at least in part due to the nonlinear nature of metabolism itself, along with ecological effects.…”
Section: Measuring Synthetic Community Yield As a Function Of Environsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that all four of our organisms experienced cases of higher than expected yields on double vs. single nutrients (Supplementary Figure 13), which may reflect capabilities of the organisms to more efficiently fulfill metabolic requirements using multiple nutrients. Our observation parallels previous instances of this effect in microbial growth rates 33,39,40 , which we also corroborated using a timecourse experiment (Supplementary Figure 14). Thus, it seems plausible that the increases in ( we observed with increasing environmental complexity are at least in part due to the nonlinear nature of metabolism itself, along with ecological effects.…”
Section: Measuring Synthetic Community Yield As a Function Of Environsupporting
confidence: 91%
“…These nonlinearities were also displayed by our communities on individual carbon sources (Supplementary Figure 10), as well as in previous studies 20,21 . Additionally, we found evidence that a similar effect could be observed for microbial growth rates ( Supplementary Figure 11), as reported previously 22,30,31 . Therefore, the increases in " may at least be partially due to the nonlinear nature of metabolism itself.…”
Section: Assembly Of Multispecies Communities and Combinatorial Nutrisupporting
confidence: 89%
“…Glucose and lactose are both highly preferable carbon sources for E. coli, both supporting large growth rates. Fructose, glycerol, maltose, and galactose are less preferred (Wang et al 2019), but isolate TG01 can use fructose as good as glucose.…”
Section: Morphological and Physiological Characteristics Of Actinomycmentioning
confidence: 99%
“…Although catabolisable amino acids are the main carbon source that support growth in LB [9], LB also contains sugar mixtures in short supply, which made it an ideal medium for our studies on nutrient limitation. These sugars are consumed one after another or co-utilized in E. coli cultures depending on their hierarchy and concentration [5,10,63]. Glucose, the preferred carbon source, is consumed first, followed by other fermentable sugars such as maltodextrins, nucleotides, and free sugars.…”
Section: Discussionmentioning
confidence: 99%